Population of Esteochilus spp. as a Base of Sustainable Fishing in Serayu River - Lestari, Windiarini; Putranto, Yogi; Setyaningrum, Nuning; Sugiharto, Sugiharto (Universitas Gadjah Mada, 2009)
The increasing demand for freshwater resources generated by human population growth, urbanization, industrialization and irrigation will result in a decline or loss of freshwater fish such as Osteochilus spp. The aims of research were to analysis the population of Osteochilus spp in terms of abundance, longitudinal distribution and sex ratio and to determine environmental factors of river driven these populations. The research was carried out in upper part of Serayu River during wet season (January – March) and dry season (June - August) 2007. Fish was collected by using electro fishing and stratified random sampling was applied by dividing this river into five strata based on altitude. The result showed that the total abundances of Osteochilus spp. was 149 individuals, it was composed by of O. hasselti (47) with 8.30 – 24.35 cm and 11.20 – 198.70 g, O. microchephalus (101) with 11.35 – 25.21 cm and 17.9 – 206.5 g and O. kahajanensis (1) with 17.30 cm and 68.80 g. The size of population O hasselti and O. microchephalus gradually increased from 7 and 4 individuals in stratum A became 27 and 12 individuals in stratum D, and then increased up to 43 and 17 individuals in stratum E. The sex ratio of O. hasselti was 10:16 and O. microchephalus was 20:23. Both species were longitudinally distributed in Serayu River. It seems that the population of O. hasellti and O. microchephalus were more influenced by physical factors i.e. depth and current rather than chemical factors i.e. DO and pH of Serayu River.